The cure : - Brantley, Timothy (John Wiley & Sons, 2007)
According to Dr. Timothy Brantley, most health problems are not caused by genetics or germs but by the standard American diet. Drawing on Brantley's groundbreaking research and his years of working with nutritional healing, The Cure contains a revolutionary step-by-step program that can flush toxins out of the body, restore balance, promote natural healing, and increase vitality.